Opportunities for earlier diagnosis of type 1 diabetes in children: A case-control study using routinely collected primary care records. Issue 3 (June 2018) - Lee, Joseph Jonathan; Thompson, Matthew James; Usher-Smith, Juliet Alexandra; Koshiaris, Constantinos; Van den Bruel, Ann
Highlights: Children developing T1DM present to UK primary care more than controls two weeks before diagnosis. Most potential diagnostic opportunities occur in the final week before diagnosis. The majority of cases are not seen in primary care during this period. Abstract: Background: The epidemiology of type 1 diabetes mellitus (T1DM) suggests diagnostic delays may contribute to children developing diabetic ketoacidosis at diagnosis. We sought to quantify opportunities for earlier diagnosis of T1DM in primary care. Methods: A matched case-control study of children (0–16 years) presenting to UK primary care, examining routinely collected primary care consultation types and National Institute for Health and Care Excellence (NICE) warning signs in the 13 weeks before diagnosis. Results: Our primary analysis included 1920 new T1DM cases and 7680 controls. In the week prior to diagnosis more cases than controls had medical record entries (663, 34.5% vs 1014, 13.6%, odds ratio 3.46, 95% CI 3.07–3.89; p < 0.0001) and the incidence rate of face-to-face consultations was higher in cases (mean 0.32 vs 0.11, incidence rate ratio 2.90, 2.61–3.21; p < 0.0001). The preceding week entries were found in 330 cases and 943 controls (17.2% vs 12.3%, OR 1.49, 1.3–1.7, p < 0.0001), but face-to-face consultations were no different (IRR 1.08 (0.9–1.29, p = 0.42)). Interpretation: There may be opportunities to reduce time to diagnosis for up to one third of cases, by up to two weeks. Diagnostic opportunities might be maximised by measures that improve access to primary care, and public awareness of T1DM.